2008
DOI: 10.1002/adfm.200701257
|View full text |Cite
|
Sign up to set email alerts
|

Individual Dissolution of Single‐Walled Carbon Nanotubes by Using Polybenzimidazole, and Highly Effective Reinforcement of Their Composite Films

Abstract: Polybenzimidazole (PBI) is shown to individually dissolve/disperse single‐walled carbon nanotubes (SWNTs) in N,N‐dimethylacetamide (DMAc), which is demonstrated by vis‐near IR absorption and photoluminescence spectroscopy and atomic force microscopy observations. By casting these dispersions, SWNTs/PBI composite films were successfully fabricated on substrates without any sign of macroscopic aggregation. The thermal stability and mechanical properties of the composite films were investigated using thermogravim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 78 publications
2
75
0
Order By: Relevance
“…Figure 2b shows a representative AFM image of the KPS-treated SWNTs. The mean diameter of the nanotubes (measured at 20 points), equal to the mean top height of nanotubes [26,27], is calculated to be 3.27 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2b shows a representative AFM image of the KPS-treated SWNTs. The mean diameter of the nanotubes (measured at 20 points), equal to the mean top height of nanotubes [26,27], is calculated to be 3.27 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[114] Polybenzimidazole (PBI) has been shown individually to dissolve/disperse SWNTs in N,Ndimethylacetamide (DMAc). [115] By casting these dispersions, SWNTs/PBI composite films were successfully fabricated on substrates without macroscopic aggregation. The addition of SWNTs to PBI does not reduce the thermal stability of the matrix film, and the mechanical properties of the PBI film were reinforced by ca.…”
Section: Conjugated Polymer-cnt Thin Filmsmentioning
confidence: 99%
“…Therefore, studies on the applications of PBI in PEMFCs are of great interests. Indeed, it has already reported that the aromatic compounds have a great potential to individually dissolve SWCNTs through a physical adsorption mechanism based on the π-π interactions (Okamoto et al, 2008). A MWCNT/PBI/Pt nanocomposite has been developed by Okamoto et al (Okamoto et al, 2009).…”
Section: Non-covalent Functionalizationmentioning
confidence: 99%
“…J.T. Wang et al, 2004), which is an good feature for increasing the rate of the proton transfer and shows great promises in improving the performance of PEMFCs (Okamoto et al, 2008). From the point of view of materials science, PBI can act as a proton-conducting material for PEMFCs that can be operative even under dry conditions above 100 o C (the PEMFC operations at higher temperatures afford many benefits such as decreased carbon monoxide poisoning of the catalyst metal NPs, increased catalytic reaction rate, easy removal of generated water, and so on (Q. , and therefore is a promising candidate as a substitution for Nafion, which is a widely used proton exchange membrane (PEM) in low-temperature PEMFC systems (Deluca et al, 2006;Heitner-Wirguin, 1996;Kerres, 2001).…”
Section: Non-covalent Functionalizationmentioning
confidence: 99%